EFEKTIFITAS KEGIATAN ROHIS DALAM MENANAMKAN NILAI-NILAI KARAKTER ISLAM SISWA DI SMA NEGERI 2 DAN SMA NEGERI 4 KABUPATEN KAUR - Yuni Hartati (IAIN Bengkulu, 2016)
The purpose of this study is: To know the student’s character, shape character values instilled Islam and integrationactivities to students through activities Rohis Rohis in SMA 2 and SMA Negeri 4 Kaur District ,. This research is descriptivequalitative research that aims to describe systematically and accurately, facts and characteristics. Research conducted attemptedto describe a situation or circumstance for the implementation of the spiritual activities of students (Rohis) and Islamic culturein school improvement efforts religious character, so that the data collected purely descriptive so it does not intend to seek anexplanation. Data collection technique used oservasi, interviews and documentation. Analysis of the data used in this study isqualitative data analysis descriptive narrative, namely the analysis of the data that are qualitative by telling and interpreting thedata that have been collected through the main points of discussion. The conclusion of this study is Based on the descriptionin the previous chapters and the observation that the author did in SMA 2 and SMA Negeri 4 Kaur District may put forwardsome conclusions as follows: Conditions characters Students at SMAN 2 Kaur character of the students in general are goodenough, will but there are some students condition code is still less do not have a high awareness. It can be seen from theresults of research interviews with informants. Characters students before planting the character values of Islam seen in SMA2 and SMA Negeri 4 Kaur District envisaged that the condition of students at that time there were some students are still lesshonest and less disciplined, are reluctant to perform their prayers in congregation, they are less sensitive to the environmentand some students violate school disciplinary rules such as wearing tight clothing, truant during school hours, bringing hp andporn video store. Rohis form of extracurricular activity: SMAN 2 Kaur District consists of: Magazine walls, boarding lightningin the month of Ramadan, for their routine that takes the form migguan, the art of reading and writing the Qur’an. SMANegeri 4 Kaur District consists of mentoring, a reflection of the heart, Rabana, boarding lightning, recitals, warning big days.Implications Rohis activities Students actively participated in Rohis, can understand the true meaning of prayer than studentswho are passive in Rohis activities, especially prayer which they did mostly after prayers. This proves that the attitude of prayerin the lives of students embedded majesty of God in Him